STRATEGI PUBLIC RELATIONS DALAM MEMBANGUN DAYA SAING DAN MUTU PENDIDIKAN PADA PERGURUAN TINGGI DI ACEH - Mukhsinuddin Mukhsinuddin; Tarmizi Tarmizi; Rahmad Syah Putra; Muhammad Furqan (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
Public Relations (PR) is one of the management functions in supporting the development and maintenance of common lines between the organization and its publics regarding the strategy, cooperation and marketing of an organization so that it is of high quality and competitive. This study aims to determine the public relations strategy in building the competitiveness and quality of education at universities in Aceh. The object of this research was conducted at one of the Universities in South West Aceh, namely STAIN Teungku Dirundeng Meulaboh, with research subjects including the Chair, Deputy Chair, Head of AUAK Section, Head of Sub Division of AUK, and Public Relations Officer. Research data collection techniques are carried out in 3 ways, namely: 1) observation; 2) questionnaire; 3) in-depth interviews; and 4) documentation study, while data analysis used 4 stages, namely: 1) data reduction; 2) data display; 3) verification; 4) and drawing conclusions. Based on the results of the study, it was found that: First, in carrying out building competitiveness and quality of education, STAIN Teungku Dirundeng Meulaboh has also compiled a Vision and Mission of Public Relations/Public Relations with the aim of raising the image of STAIN Teungku Dirundeng in the eyes of the community, and formulating a plan (plan ) public relations in the form of work programs and activities involving all sections of Public Relations to develop programs referring to the Vision, Mission, Goals and Objectives of STAIN Teungku Dirundeng Meulaboh. Second, STAIN Teungku Dirundeng Meulaboh has implemented a public relations strategy in building the competitiveness and quality of education in Aceh in the form of programs and activities including the following: 1) Media and Inter-Institutional Relations; 2) Internal Relations; and 3) Media Publication and Production. The implementation of the program is also carried out based on the annual public relations plan and a fixed schedule plan for STAIN Teungku Dirundeng which contains activities that will be carried out every week, month and year on a regular basis.